The principle of legal characterization and its boundaries in tax law in light of the case law of the Court of Justice of the European Union - Márquez Lasso, Daniel E. (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The principle of legal characterization is established as an ex lege power of the Tax Administration, enabling it to determine the existence and precise configuration of the actual taxable event, irrespective of the form or designation assigned to it by the parties. Since characterization entails an essential interpretative operation and constitutes a clearly anti-avoidance legal mechanism, it must be borne in mind that the influence of European Union law in this area lies precisely in delimiting the scope of such provisions. Accordingly, legal characterization is to be understood as a power subject, inter alia, to the principles of legal hermeneutics and further constrained by a set of limits specifically intended to preclude its abusive application.
Keywords: Legal characterization; sham; antiabuse rule; abuse of law; business purpose test